ПОЛІПШЕННЯ ДИНАМІКИ СИСТЕМ ЕЛЕКТРОПРИВОДУ НА БАЗІ СИНХРОННОГО ДВИГУНА З ПОСТІЙНИМИ МАГНІТАМИ ПРИ ВИКОРИСТАННІ ОПТИМАЛЬНИХ СТРАТЕГІЙ КЕРУВАННЯ - Толочко, О.І.; Бугровий, А.А. (Інститут електродинаміки НАН України, Київ, 2016)
For synchronous motors with permanent magnet built-in rotor made comparison of the dynamic properties of typical vector control systems (maintaining flux-component of the stator current at zero) and systems using optimal control strategies. Theoretically was proved methods of improving dynamic properties of the systems with optimum energy performance by adjusting the algorithm of the speed controller. References 4, figures 3.